Modelo binomial para la valoración de empresas y los efectos de la deuda: escudo fiscal y liquidación de la firma - Silverio Milanesi, Gastón (2014)
This paper proposes a binomial model for company valuation, projecting scenarios of continuity or insolvency of the company, and comparing it with the discounted cash flow model. The Real Option Theory is used for estimating the value of the company, which results in an explicit trade-off between the advantages and the risk of taking on debts. The work is organized as follows: the model is introduced and developed, and then it is illustrated with the application of a case, comparing the results obtained with the discounted cash flow model. Variables like: leverage, tax rate and volatility are sensitive when analyzing the impact on the value of the company. Finally, the document describes the advantages of the proposed model. DOI: http://dx.doi.org/10.1016/j.jefas.2014.03.004